2019
DOI: 10.18502/kss.v3i17.4665
|View full text |Cite
|
Sign up to set email alerts
|

Developing Media of Social Science Learning Based Macromedia Flash to Increase Interest, Motivation and Learning Outcomes of Fourth Grade Elementary School

Abstract: Media of social science learning based macromedia flash can increase interest, motivation and learning outcomes of fourth graders of elementary school. This type of research is R & D research by adapting Borg & Gall development procedures. The subjects of this study are students and grade 4 students of State Elementary School of Sendangadi 1 and SD Negeri Sendangadi 2. Data collection is done by interview, questionnaire and test. Data analysis technique using MANOVA test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to (Nurhasana, 2021) Learning outcomes are the results obtained from learning activities. Study Hopefully it can bring change .…”
Section: Student Learning Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Nurhasana, 2021) Learning outcomes are the results obtained from learning activities. Study Hopefully it can bring change .…”
Section: Student Learning Resultsmentioning
confidence: 99%
“…According to (Nurhasana, 2021) Motivation is aspect important from teaching and learning . Students who have no motivation No will try For study and struggle For can understand the material taught by the teacher, on the contrary motivated students _ tall will like to school and easy absorb material in the learning process .…”
Section: Motivation Study Studentmentioning
confidence: 99%
“…The second relavant research, from Canisius Supardi in 2010 on the use of visual media to encourage and increase learning outcomes elementary science class V students [5]. The results showed that visual media can increase students' interest and learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%